2017
DOI: 10.1016/j.abrep.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of adherence to methadone maintenance treatment over a 15-year period among homeless adults experiencing mental illness

Abstract: BackgroundMethadone maintenance treatment (MMT) has important protective effects related to reduced illicit opioid use, infectious disease transmission, and overdose mortality. Adherence to MMT has not been examined among homeless people. We measured MMT adherence and reported relevant characteristics among homeless adults experiencing mental illness in Vancouver, British Columbia, Canada.Material and methodsHomeless adults living with mental illness who had received MMT prior to the baseline interview of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…To combat the drug use and reduce the HIV/ AIDS among high-risk behavior community, methadone maintenance treatment (MMT) has been launched since 2008 [5,6]. Several studies showed the benefits of MMT maintenance worldwide: reduced HIV transmission among drug injecting users and criminal activities caused by drug users [7]; helped reducing death rates, morbidity and social illness or being homeless [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To combat the drug use and reduce the HIV/ AIDS among high-risk behavior community, methadone maintenance treatment (MMT) has been launched since 2008 [5,6]. Several studies showed the benefits of MMT maintenance worldwide: reduced HIV transmission among drug injecting users and criminal activities caused by drug users [7]; helped reducing death rates, morbidity and social illness or being homeless [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In China, the medication adherence rate has ranged from 11.8% at 8 years in Xi'an (14 clinics, 2006-2013) [18] to 26.57% at 5 years in Yunnan (1 clinic, 2007-2011). In Canada, a 15-year research found a very low rate of adherence to MMT among homeless adults with mental illness [10]. In Vietnam, the level of incomplete MMT adherence was various from the big city (from 8.3 to 17.7%) [11] to the mountainous setting (37.7%) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the general population, homeless individuals have lower food security (14), lower nutrient intake, and diet insu ciency (15,16). Homeless individuals typically cannot access kitchens to prepare meals and preserve perishable foods (17,18), forcing them to depend on fast food, shelter or community meals, even food waste to meet their needs, or to remain hungry (19)(20)(21). The intertwinement of homelessness with mental illness and substance use worsens access to food because it generates competing needs for purchasing medications and substances (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Recovery could in 1 crease rates of patient dropout and discharge as well as discourage people not currently in treatment from signing up (Frank 2018). MMT in the U.S. is already criticized for its strict rules and time-consuming, intrusive approach (Parpouchi et al 2017;Callon et al 2006) as evidenced by its consistently low rates of use and retention, particularly when compared to other countries using less-regulated approaches (Saloner and Karthikeyan 2015). Thus, the use of Recovery in MMT may make an already over-regulated and overly-cumbersome treatment even more so precisely when it is most needed.…”
Section: Introductionmentioning
confidence: 99%